Parental Autonomy Granting and School Functioning among Chinese Adolescents: The Moderating Role of Adolescents’ Cultural Values - Wang, Cixin; Do, Kieu Anh; Bao, Leiping; Xia, Yan R.; Wu, Chaorong (Frontiers in Psychology, 2017)
Abstract School adjustment and achievement are important indicators of adolescent well-being; however, few studies have examined the risk and protective factors predicting students’ school adjustment and achievement at the individual, familial, and cultural level. The present study examined the influences of individual and familial factors and cultural values on Chinese adolescents’ school functioning (e.g., school adjustment and grades). It also tested whether cultural values moderated the relationship between parenting and adolescents’ school functioning. Self-report data were collected from a stratified random sample of 2,864 adolescents (51.5% female, mean age =15.52 years, grade 6th – 12th) from 55 classrooms, in 13 schools in Shanghai, China. Results showed that self-esteem (bse adj = .05, SE = .01, p < .001; bse grades = .08, SE = .02, p < .001), parent-adolescent conflict (bconflict adj = -.03, SE = .00, p < .001; bconflict grades = -.04, SE = .01, p < .001), and conformity to parental expectations (bconform adj = -.03, SE = .02, p < .05; bconform grades = .10, SE = .04, p <.05) all had significant effects on both school adjustment and grades respectively. More importantly, results showed that independent self-construal moderated the relationship between parental autonomy granting and adolescents’ grades (bindepdent x autom = .06, SE = .02, p <.01). The findings suggest that cultural values may influence adolescents’ appraisal of parental autonomy granting, which then impacts their school functioning.